Penerapan Model Pembelajaran Matematika Knisley (MPMK) Untuk Meningkatkan Kemampuan Komunikasi Matematis Siswa SMP - Tasia, Tasia; Ramlah, Ramlah; Ardiyanti, Yusi (Delta: Jurnal Ilmiah Pendidikan Matematika, 2024)
The right learning model helps student mathematical communication skills in mathematics learning to improve. The knisley mathematics learning model is one model that can be used as a reference because the learning process is based on experience. Thus, the purpose of this study is to examine the achievement and improvement of students’ mathematical communication skills who get the Knisley Mathematics Learning Model better than students who get conventional learning. The research method used is the experimental method. The population in this study were all students of VIII grade at one of the junior high schools in East Karawang, while the sample was taken from two classes randomly using cluster random sampling, obtained by VIII K class as the experimental class and VIII A class as the control class. The design in this study used a pretest-posttest control group design with a quantitative approach. The data were processed using Microsoft Excel 2007 software and SPSS software version 21 for windows. The data analysis in this used the normality test, homogeneity test, two-mean difference test, and n-gain data analysis. The results of this study indicate that the achievement of mathematical communication skills of students who get the Knisley Mathematics Learning Model is better than students who get conventional learning, as well as the increase in mathematical communication skills of students who get the Knisley Mathematics Learning Model is higher than students who get conventional learning. This means that the Knisley Mathematics Learning Model is effective in achieving and improving junior high school students’ mathematical communication skills.